PERKEMBANGAN SISTEM KEPEGAWAIAN NEGARA - Janry Haposan U.P Simanungkalit (Badan Kepegawaian Negara | The National Civil Service Agency, 2007)
The role and position of civil service system really essential, strategic, and as critical success factor in every state bureaucracy. Pros and cons bureaucracy of a state really being regarded by quantity and also quality of civil service. Therefore, bureaucracy ability to do reform in order to improve comprehensively and continuously really been charged, that one of its is by learning best practices to civil service reform various state. This article seeks to advance the analysis of developing civil service system in comparability perspective among United States of America and Indonesi, beginning of developing civil service system of each state, position/job classification, recruitment and selection, promotion/carrier, remuneration, and training and development. At the end of this article as lesson learned to Indonesian is recommended some critical notes that needs and have to expedited civil service reform for the future. Keywords: Civil Service System, Reform, Promotion/Carrier, Remuneration, and Training and Development, Merit System, United States of America, Indonesia.